2001
DOI: 10.2307/3583197
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gardnerella vaginalis in Pregnant Nigerian Women

Abstract: The prevalence of Gardnerella vaginalis in the genital tract of 253 pregnant Nigerian women was 17.0 % (43). The highest prevalence occurred among women aged 16-20 years (26%) while the lowest occurred among those aged 31-35 years (13%). Women aged 30 years and below had an overall prevalence of 18.2% while those above 30 years had a prevalence rate of 12.7%. This difference was not significant (χ 2 = 0.66; p = 0.42). There was a decline in the prevalence rate of G. vaginalis with increasing gestational age be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
3
20
1
Order By: Relevance
“…This study demonstrates that bacterial vaginosis is common among pregnant women in Ebonyi State, Nigeria commoner than was previously documented [24] [25]. Studies have shown that awareness of BV is low among pregnant women and physicians alike [39].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This study demonstrates that bacterial vaginosis is common among pregnant women in Ebonyi State, Nigeria commoner than was previously documented [24] [25]. Studies have shown that awareness of BV is low among pregnant women and physicians alike [39].…”
Section: Resultsmentioning
confidence: 57%
“…This gave an incidence of 23.9%. This incidence is not consistent with that of Adinma et al in Nnewi, south east Nigeria 17% [24] and Adeoye et al 10.5% [25] but is consistent with incidences of 25% [26] and 23% [27] When the mother's level of education and the incidence of BV was subjected to statistical analysis, it was found to be significant (Chi square-0.51, df-3, P-0.04). When the educational level of the mother was matched against douching; there was a steady increase in the number that douched as the educational level increased.…”
Section: Discussionmentioning
confidence: 69%
“…Of greater clinical importance is the link between BV and HIV infection. Apart from its association with adverse pregnancy outcomes, BV is associated with increased risk of sexual acquisition of HIV [1,3,8]. There is evidence to support several mechanisms through which BV and other reproductive tract infections facilitate HIV transmission [7].…”
Section: Introductionmentioning
confidence: 99%
“…In BV, however, increased numbers of bacteria, such as Gardnerella vaginalis, Bacteroides spp, Mobiluncus spp, Prevotella spp and Mycoplasma hominis, replace them [1]. The reported prevalence of BV in pregnant women ranges from 14% to 21% in Western countries [2][3][4], and a prevalence rate of 40.8% was reported in a non-pregnant population in southern Nigeria [5]. A case study done in Ghana showed a low prevalence of 1.4% among antenatal women [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation